2020
DOI: 10.1186/s12885-020-07443-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of breast MRI for surgical decision in patients with breast cancer: ductal carcinoma in situ versus invasive ductal carcinoma

Abstract: Background Preoperative breast magnetic resonance imaging (MRI) provides more information than mammography and ultrasonography for determining the surgical plan for patients with breast cancer. This study aimed to determine whether breast MRI is more useful for patients with ductal carcinoma in situ (DCIS) lesions than for those with invasive ductal carcinoma (IDC). Methods A total of 1113 patients with breast cancer underwent mammography, ultrasonography, and additional breast MRI before surgery. The patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…In current study, there is a positive role of MRI at surgical plan (66.6%) at surgical plan according to the type of surgery after pathological correlation by identifying additional occult malignant findings (20 cases are converted from breast conserving surgery and oncoplastic technique to extreme oncoplastic technique or mastectomy). Likewise, another recent study conducted by Lee and Colleagues [16] , on a total of 1113 cases with breast cancer who were undergone mammography, US, and breast MRI prior to surgical procedure. They have concluded that, changes (either by increase or by decrease) in surgical approaches were very common in the ductal carcinoma in situ group in comparison with the invasive ductal carcinoma group, subsequent to increase in the size of suspicious lesions on breast MRI, recognition of further daughter nodules, multifocality or multicentricity, and suspicious signs on mammography or US but benign signs on breast MRI.…”
Section: Case Presentationmentioning
confidence: 99%
“…In current study, there is a positive role of MRI at surgical plan (66.6%) at surgical plan according to the type of surgery after pathological correlation by identifying additional occult malignant findings (20 cases are converted from breast conserving surgery and oncoplastic technique to extreme oncoplastic technique or mastectomy). Likewise, another recent study conducted by Lee and Colleagues [16] , on a total of 1113 cases with breast cancer who were undergone mammography, US, and breast MRI prior to surgical procedure. They have concluded that, changes (either by increase or by decrease) in surgical approaches were very common in the ductal carcinoma in situ group in comparison with the invasive ductal carcinoma group, subsequent to increase in the size of suspicious lesions on breast MRI, recognition of further daughter nodules, multifocality or multicentricity, and suspicious signs on mammography or US but benign signs on breast MRI.…”
Section: Case Presentationmentioning
confidence: 99%
“…[18,19]. However, several studies have investigated and proved the efficacy of MRI in detecting and assessing the size of DCIS [20,21]. The sensitivity of MRI in the detection of DCIS was approximately 77%-96% in those studies.…”
Section: Univariable and Multivariable Analyses Of Factors For A Posi...mentioning
confidence: 99%
“…While DCIS is literally an 'in situ neoplastic proliferation of ductal-lobular epithelial cells', its ability to be invasive ductal carcinoma (IDC) should always be considered. A suspicious DCIS features on mammogram should be sufficient for the physician to consider MRI or MFBI before any histopathological measures are taken (38)(39)(40). Special cases such as metastatic disease or elevated liver function biomarkers, should warrant contrast-enhanced MRI on the respective area of suspicious metastatic foci (7).…”
Section: Pre-treatment Mfbimentioning
confidence: 99%